Bridging the Digital Divide: Digital Media Literacy among College Students in Nepal - Bhandari, Bhuwan (KMC Journal, 2025)
Digital literacy includes a wide range of concepts that feature different meanings and the ability to use digital tools and applications, examining digital media literacy among college students and its impact on the access disparity. The objective of the study was to enable students to effectively utilize digital tools and comprehend the benefits and responsibilities associated with being informed consumers. A quantitative methodology was employed, gathering data via a survey and closed-ended questionnaire from a sample of 106 undergraduate students in the Humanities and Social Sciences studying at Kailali Multiple Campus. The survey assesses students’ opinions on digital media literacy, emphasizing the utilization of digital tools and the acknowledgment of the necessity to be informed, involved and responsible. The results show that 53.8% of participants view media literacy as an essential analytical ability, 61.2% rely on search engine optimization to find resources as the most reliable source, 70.2% access digital content via mobile devices, and 45.6% consider digital citizenship an important aspect of digital literacy. The results explore how teaching digital literacy can help close these gaps and guarantee that people’s daily lives include access to digital skills. The findings of the study suggest improving students’ ability to locate, evaluate, synthesize and use information in practical situations.